2021
DOI: 10.3390/atmos12010118
|View full text |Cite
|
Sign up to set email alerts
|

Public Health Considerations for PM10 in a High-Pollution Megacity: Influences of Atmospheric Condition and Land Coverage

Abstract: This paper analyzes the PM10 concentrations and influences of atmospheric condition (AC) and land coverage (LC) on a high-pollution megacity (Bogota, Colombia) from a public health viewpoint. Information of monitoring stations equipped with measuring devices for PM10/temperature/solar-radiation/wind-speed were used. The research period lasted eight years (2007–2014). AC and LC were determined after comparing daily PM10 concentrations (DPM10) to reference limits published by the World Health Organization (WHO).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
0
4
0
1
Order By: Relevance
“…This differential behavior between the south and north in relation to PM concentrations may be associated with the local behavior of climate variables such as wind speed and direction, and relative humidity. For example, it was reported that the northern zone of the megacity historically showed the highest wind speeds [4]. In the case of O3 and SO2 concentrations, differences in the moving average term between nearby monitoring stations were observed ('q' between 1 month -18 months).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This differential behavior between the south and north in relation to PM concentrations may be associated with the local behavior of climate variables such as wind speed and direction, and relative humidity. For example, it was reported that the northern zone of the megacity historically showed the highest wind speeds [4]. In the case of O3 and SO2 concentrations, differences in the moving average term between nearby monitoring stations were observed ('q' between 1 month -18 months).…”
Section: Resultsmentioning
confidence: 99%
“…Each territory has a unique atmospheric dynamic due to its particular meteorological and orography conditions, and that is why it is necessary to study in a differentiated way the regulatory interventions in favor of urban air quality [4]. In this particular case of atmospheric physics, regulatory intervention is interpreted as the occurrence of an exogenous and induced event to the historical behavior of air quality variables [5].…”
Section: Introductionmentioning
confidence: 99%
“…During the study period, there was a restriction on the circulation of vehicles in the megacity as a measure to reduce traffic congestion. This vehicular restriction prevented about 40% of the passenger cars of the megacity from circulating (between 6 and 9 a.m. and 3 and 7 p.m.) [45].…”
Section: Study Sitementioning
confidence: 99%
“…Asimismo, la concentración de material particulado PM10 y PM2.5 es una de las principales causas de este tipo de problemas (Sosa et al, 2017;Mukherjee y Agrawal, 2017), siendo los niños los más afectados (Mahapatra et al, 2020;Manisalidis et al, 2020) A nivel mundial, las infecciones respiratorias agudas (IRA) se encuentran entre los principales problemas de salud pública (Soriano et al, 2020), mientras que las emisiones de partículas por fuentes móviles son uno de los principales problemas Área Ambiental de calidad del aire (Pineda, 2018). En Colombia, particularmente en las ciudades de Bogotá (Colla et al, 2021;Mangones et al, 2020;Zafra et al, 2021) y Medellín (Gil et al, 2020;Hernández et al, 2020), se registran correlaciones significativas del PM2.5 con las muertes de tipo cardiovascular y pulmonar. De lo mencionado se destaca que, en la mayoría de los casos, los estudios sobre los efectos del material particulado se concentran en las grandes ciudades de Colombia sin tener en cuenta que las ciudades intermedias pueden presentar efectos iguales (Rodríguez, 2018).…”
Section: Fuente: Autoresunclassified